Global buckling and residual capacities of circular recycled aggregate concrete-filled stainless steel tube (RACFSST) columns after exposure to fire - Wang, Ziyi (2025)
The post-fire flexural buckling behaviour and capacities of circular recycled aggregate concrete-filled stainless steel tube (RACFSST) columns are studied in this paper, underpinned by testing and numerical modelling. A testing programme was firstly conducted on twelve column specimens designed with three recycled coarse aggregate replacement ratios (0%, 35% and 70%), including nine column specimens after exposure to the ISO 834 standard fire for 15 min, 30 min and 45 min and three reference column specimens at ambient temperature. The test failure modes, load–mid-height lateral deflection curves and failure loads were reported in detail. The influences of heating durations and recycled coarse aggregate replacement ratios on failure loads and mid-height lateral deflections at failure loads of circular RACFSST column specimens were discussed and their lateral deflection distributions were analysed. The testing programme was followed by a numerical modelling programme, where thermal and mechanical finite element models were developed to repeat the experimental results and afterwards used to carry out parametric studies to generate a numerical data pool over a wide range of cross-section dimensions and member lengths. Based on the test and numerical data, the relevant design rules for circular natural aggregate concrete-filled carbon steel tube columns at ambient temperature, as specified in the European code, Australian/New Zealand standard and American specification, were evaluated, using post-fire material properties, for their applicability to circular RACFSST columns after exposure to fire. It was revealed from the evaluation results that the three design codes led to overall acceptable levels of accuracy and consistency in predicting post-fire flexural buckling capacities of circular RACFSST columns, but with some unsafe predictions.